Applied illumination engineering - Lindsey, Jack L (Fairmont Press ; Distributed by Prentice Hall PTR, 1997)
This comprehensive reference provides a practical, fully illustrated guide to design, specification, and application of state-of-the-art lighting, from the fundamentals of illumination to hands-on application. The full scope of light sources is examined and basic design methods for both indoor and outdoor lighting are presented, along with optimum application strategies for merchandise, offices, industrial settings, floodlighting, parking lots and street lighting. The second edition features a new chapter on skylights for industrial buildings, covering layout parameters and daylight availability calculations used to predict skylight performance. The chapter on lighting retrofits has been revised to emphasize methods for analyzing potential retrofits, examining how retrofit results can be predicted, how to evaluate retrofit proposals, and how to avoid common mistakes. Lighting maintenance, as well as the economics of lighting design, including life cycle cost analysis, are also covered.